ACTUALIZATION OF ISLAMIC VALUES IN THE FORMATION OF CHARACTER OF SENIOR HIGH SCHOOL ERA NOW - Musradinur Musradinur (STAI Al-Washliyah Banda Aceh, 2020)
The moral decline of the younger generation needs more intensive handling and need to instill moral values as early as possible, including in Aliyah madrassas. The problems faced by students today are more complex than before, the phenomenon of association and student clothing today is very unsettling to the world of education, therefore the role of teachers as educators in madrasas is very central and strategic in changing phenomena that occur today, not just limited to energy educators in madrasas even teachers become parents of students when parents have entrusted their children to be educated and always advise in truth and advise in patience, so that in madrasas still maintain an academic culture based on Islamic values. Educational institutions are not only obliged to improve academic quality, but also responsible for shaping the character of students. Academic quality and good character building are two integral missions that should receive the attention of educational institutions. However, the economic and political guidance of education led to an emphasis on academic achievement overcoming the ideal role of educational institutions in character formation. Habit in moral cultivation is an important stage that should accompany the development of each subject. Teaching morals without habituation does so, it only sows seeds into the middle of the ocean, because morals are not just knowledge, but moral habituation. Facilitation trains students to overcome these problems. Activities undertaken by students in implementing facilitation methods have a positive impact on the personality development of students.